Religious Activities At The Al Karomah Martapura Grand Mosque, Banjar Regency - Muhammad Hartono; Syaharuddin Syaharuddin; Jumriani Jumriani; Fatwa Nur’aini; Sovia Husni Rahmia (Universitas Lambung Mangkurat, 2025)
The mosque is a place for Muslims to prostrate and carry out worship. The Al Karomah Martapura Grand Mosque is one of the large mosque buildings in Banjar regency. The Al Karomah Martapura Grand Mosque has many religious activities that are carried out such as carrying out various congregational prayers, reciting the Qur'an, breaking the fast together, Zakat Fitrah, Slaughtering Sacrificial Animals, Religious Recitations, and Islamic Religious Holiday Activities. However, there are still people who do not know what activities are carried out at the Al Karomah Martapura Grand Mosque. The purpose of writing is to describe the environment in the mosque and the activities carried out in the mosque. The approach used in this study is a qualitative approach using a type of descriptive research. Data collection was carried out through observation, interviews with the community around the mosque, documentation, analysis through reduction, presentation of data in the form of text equipped with pictures and tables, and drawing conclusions. Test the validity of the data by extending observations, member checks, and triangulation. The results of this study explain that the Al Karomah Grand Mosque is not only used as a place of prayer but also many other religious activities so that it can be used as an example for other mosques so that the mosque can be used properly to become a place for Muslims to carry out worship. The Al Karomah Martapura Grand Mosque can also help address social problems such as deviant attitudes and behaviors, poverty, natural disasters, and conflicts.Keywords : Activities; Religion; Mosque